Woody residues of the grape production chain as an alternative precursor of high porous activated carbon with remarkable performance for naproxen uptake from water (2021)
Activated carbon prepared from grape branches was used as a remarkable adsorbent to uptake naproxen and treat a synthetic mixture from aqueous solutions. The material presented a highly porous texture, a surface area of 938 m2 g−1 , and certain functional groups, which were key factors to uptake naproxen from effluents. The maximum adsorption capacity predicted by the Langmuir model for naproxen was 176 mg g−1. The thermodynamic study revealed that the adsorption process was endothermic and spontaneous. The linear driving force (LDF) model presented a good statistical adjustment to the experimental decay data. A suitable interaction pathway of naproxen adsorption onto activated carbon was proposed. The adsorbent material was highly efficient to treat a synthetic mixture containing several drugs and salts, reaching 95.63% removal. Last, it was found that the adsorbent can be regenerated up to 7 times using an HCl solution. Overall, the results proved that the activated carbon derived from grape branches could be an effective and sustainable adsorbent to treat wastewaters containing drugs.